Synaptic plasticity alterations associated to memory impairment induced by deletion of CB2 cannabinoid receptor - Garcia Gutierrez, María S. (2013)
In this study, the role of CB2r on aversive memory consolidation was further evaluated. Mice lacking CB2r (CB2KO) and their corresponding littermates (WT) were exposed to the step-down inhibitory avoidance test (SDIA). MAP2, NF200 and synaptophysin (SYN)-immunoreactive ﬁbers were studied in the hippocampus (HIP) of both genotypes. The number of synapses, postsynaptic density thickness and the relation between the synaptic length across the synaptic cleft and the distance between the synaptic ends were evaluated in the HIP (dentate gyrus (DG) and CA1 ﬁelds) by electron microscopy. Brainderived neurotrophic factor (BDNF), glucocorticoid receptor (NR3C1) gene expressions and mTOR/ p70S6K signaling cascade were evaluated in the HIP and prefrontal cortex (PFC). Finally, the effects of acute administration of CB2r-agonist JWH133 or CB2r-antagonist AM630 on memory consolidation were evaluated in WT mice by using the SDIA. The lack of CB2r impaired aversive memory consolidation, reduced MAP2, NF200 and SYNimmunoreactive ﬁbers and also reduced the number of synapses in DG of CB2KO mice. BDNF and NR3C1 gene expression were reduced in the HIP of CB2KO mice. An increase of p-p70S6K (T389 and S424) and p-AKT protein expression was observed in the HIP and PFC of CB2KO mice. Interestingly, administration of AM630 impaired aversive memory consolidation, whereas JWH133 enhanced it. Further functional and molecular assessments would have been helpful to further support our conclusions. These results revealed that CB2r are involved in memory consolidation, suggesting that this receptor could be a promising target for developing novel treatments for different cognitive impairmentrelated disorders.